Advancing river monitoring using image-based techniques: challenges and opportunities - Salvatore Manfreda; Domenico Miglino; Khim Cathleen Saddi; Seifeddine Jomaa; Anette Eltner; Matthew Perks; Salvador Peña-Haro; Thom Bogaard; Tim H.M. van Emmerik; Stefano Mariani; Ian Maddock; Flavia Tauro; et al. (Hydrological Sciences Journal, 2024)

Field-based monitoring of instream leaky barrier backwater and storage during storm events - Valentine Muhawenimana; Elizabeth Follett; Ian Maddock; Catherine A.M.E. Wilson (Journal of Hydrology, 2023)

Do legacy effects of deposited fine sediment influence the ecological response of drifting invertebrates to a fine sediment pulse? - Victoria S. Milner; Ian P. Maddock; Iwan Jones; George C. Bunting (Aquatic Sciences, 2021)
The deposition of excess fine sediment and clogging of benthic substrates is recognised as a global threat to ecosystem functioning and community dynamics. Legacy effects of previous sedimentation create a habitat template on which subsequent ecological responses occur, and therefore, may have a long-lasting influence on community structure. Our experimental study examined the effects of streambed colmation (representing a legacy effect of fine sediment deposition) and a suspended fine sediment pulse on macroinvertebrate drift and community dynamics. We used 12 outdoor stream mesocosms that were split into two sections of 6.2 m in length (24 mesocosm sections in total). Each mesocosm section contained a coarse bed substrate with clear bed interstices or a fine bed substrate representing a colmated streambed. After 69 days, a fine sediment pulse with three differing fine sediment treatments was applied to the stream mesocosms. Added fine sediment influenced macroinvertebrate movements by lowering benthic density and taxonomic richness and increasing drift density, taxonomic richness, and altering drift assemblages. Our study found the highest dose of sediment addition (an estimated suspended sediment concentration of 1112 mg l −1 ) caused significant differences in benthic and drift community metrics and drift assemblages compared with the control treatment (30 l of water, no added sediment). Our results indicate a rapid response in drifting macroinvertebrates after stressor application, where ecological impairment varies with the concentration of suspended sediment. Contrary to expectations, bed substrate characteristics had no effect on macroinvertebrate behavioural responses to the fine sediment pulse.

Long-term changes in social interaction and reward following repeated MDMA administration to adolescent rats without accompanying serotonergic neurotoxicity - Kevin Fone; Simon Beckett; Ian Topham; Jennifer Swettenham; Melanie Ball; Laura Maddocks (Psychopharmacology, 2002)